Experimental results of an adaptive resource allocation - Tereso, Anabela Pereira (2003)
We describe the structure and the implementation aspects of the dynamic programming procedure that was proposed in a previous report (Tereso et al., 2001) for the optimal resource allocation to activities under the assumption of stochastic work content. We illustrate its implementation to five projects of varying size, which exhibit the computational complexity of the procedure. The pseudo-code may be obtained by request from the lead author.